Flipped Learning Sebagai Bentuk Pembelajaran Blended di Era Digital (Suatu Tinjauan Konseptual) - Irna Sjafei (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study is used to review the concepts of flipped learning and blended learning and to determine the extent to which the concept of flipped learning is a description of blended learning. To achieve this goal, this study describes conceptually about flipped learning and blended learning. Based on the analysis of the concept of flipped and blended learning, then build a linkage construct between the concept of flipped learning which is applied by blended learning with reference support. The implementation of these learning strategies uses Information and Communication Technology (ICT) in various digital platforms that have developed to date. The use of ICT that responds to various learning models also changes various learning strategies in the form of blended learning and fully online. Leaning Content Management System (LCMS) assistance whose applications have been properly installed and easy to access as a form of learning management. Blended learning involves face-to-face and online learning, where both are used to complement each other so as to create an interesting learning environment. Flipped learning is one form of applying blended learning. The current development is known as flipped blended.